2018
DOI: 10.3390/batteries4010008
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Na0.44MnO2 Slabs for Sodium-Ion Batteries Obtained through Urea-Based Solution Combustion Synthesis

Abstract: Abstract:One of the primary targets of current research in the field of energy storage and conversion is the identification of easy, low-cost approaches for synthesizing cell active materials. Herein, we present a novel method for preparing nanometric slabs of Na 0.44 MnO 2 , making use of the eco-friendly urea within a solution synthesis approach. This kind of preparation greatly reduces the time of reaction, decreases the thermal treatment temperature, and allows the obtaining of particles with smaller dimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…In order to improve the electrochemical properties of sodium ion intercalation, subsequent studies focused on reducing the particle size of Na 0.44 MnO 2 in order to shorten the sodium diffusion pathway while increasing the electrode/electrolyte solution interfacial specific area (thus increasing interfacial charge transfer kinetics) [32d] . In addition, various Na 0.44 MnO 2 nanomaterials were synthesized including nanorods, [30a,37a,47] nanometric slabs, [48] nano‐sized powder, [36,42a,49] nanowires, [32a,c,50] ultra‐long submicron slabs, [30b] multangular rods, [39b] and nanofibers [37a] …”
Section: Sodium‐ion Battery Applicationsmentioning
confidence: 99%
“…In order to improve the electrochemical properties of sodium ion intercalation, subsequent studies focused on reducing the particle size of Na 0.44 MnO 2 in order to shorten the sodium diffusion pathway while increasing the electrode/electrolyte solution interfacial specific area (thus increasing interfacial charge transfer kinetics) [32d] . In addition, various Na 0.44 MnO 2 nanomaterials were synthesized including nanorods, [30a,37a,47] nanometric slabs, [48] nano‐sized powder, [36,42a,49] nanowires, [32a,c,50] ultra‐long submicron slabs, [30b] multangular rods, [39b] and nanofibers [37a] …”
Section: Sodium‐ion Battery Applicationsmentioning
confidence: 99%
“…Although Na x MnO 2 materials exhibit high capacities nearing 200 mAh g 1 , this capacity is often lost over the initial charge/ discharge cycles due to strain from Mn 3+ Jahn-Teller distortions. [102] Various attempts to mitigate the structural changes range from tailoring the morphology via modified solidstate synthesis, [103][104][105] sol-gel methods, [106] hydrothermal methods, [107,108] and more, [109][110][111] or using dopants such as Bi, [112] F, [113] and Fe. [114] Ferrara et al observed an increase in capacity from 85.0 to 95.0 mAh g −1 at a charge rate of 2C by switching from a traditional solid-state synthesis method to an ecofriendly urea-based solution synthesis.…”
Section: Namnomentioning
confidence: 99%
“…[114] Ferrara et al observed an increase in capacity from 85.0 to 95.0 mAh g −1 at a charge rate of 2C by switching from a traditional solid-state synthesis method to an ecofriendly urea-based solution synthesis. [111] However, the capacity retention is limited to 75.7% over 200 cycles. Furthermore, Ma et al demonstrated that Na 0.44 MnO 2 nanorods formed using MnCO 3 derived from a hydrothermal synthesis method show higher capacity and capacity retention than those derived from coprecipitation methods.…”
Section: Namnomentioning
confidence: 99%
“…Thirdly, this method can be turned into a flow process, which makes it industrially scalable [13]. The GNP and its variations have been used by the solid-oxide fuel cell research community [13,17,18] and to some extent by the battery community to synthesize and study materials like NaTi3(PO4)3 [19], Li(Ni1/3Mn1/3Co1/3-xNax)O2 [20], LiNi1/3Co1/3Mn1/3O2 (urea as fuel) [21], Li4Ti5O12 (lactic acid as fuel) [22], substituted Na0.44MnO2 bronzes [23][24][25][26], Na0.44MnO2 (urea as fuel) [27] and ZnFe2O4 [28]. This paper is the first report to our knowledge that successfully utilizes the GNP method to produce a NVP cathode material and characterize it in half and full cells.…”
Section: Synthesis Of Na 3 V 2 (Po 4 )mentioning
confidence: 99%